2012
DOI: 10.3109/13625187.2012.750290
|View full text |Cite
|
Sign up to set email alerts
|

Is counselling necessary? Making the decision to have an abortion. A qualitative interview study

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 12 publications
2
53
0
3
Order By: Relevance
“…This is not surprising since research has previously shown that most women make a decision on the outcome of an unintended pregnancy at the time of taking a pregnancy test 9 16. Separate Swedish and American studies found that three-quarters of women have decided on a provisional course of action even before taking a pregnancy test 17 18.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is not surprising since research has previously shown that most women make a decision on the outcome of an unintended pregnancy at the time of taking a pregnancy test 9 16. Separate Swedish and American studies found that three-quarters of women have decided on a provisional course of action even before taking a pregnancy test 17 18.…”
Section: Discussionmentioning
confidence: 97%
“…opposed to abortion) charities. Although it is understood that only a minority of women in the UK who are considering an abortion actually use counselling services, there has been little research to quantify the exact proportion of women who do so 9 16…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our own research suggests that counselling may not be voluntary, at least at the facilities where our research was conducted. Given that abortion seekers have varying needs and in order to uphold reproductive autonomy, mandatory counselling is certainly undesirable (Brown, ). Echoing Moore et al's () argument for a 'cafeteria‐style approach' and Birdsey et al's () call for client‐centred counselling, a model of abortion counselling should be developed that is responsive to the narratives clients tell of their lives.…”
Section: Implications For Pre‐abortion Counselling Service Provisionmentioning
confidence: 99%
“…A consistent finding is that women reach decisions about their pregnancies based on the specific relational contexts of their own lives (Hoggart, 2012; Lattimer, 1998; Lee, 2004; Lee, Clements, Inghan, & Stone, 2004; Purcell, Cameron, et al., 2014). In contrast with the law’s medicalised construction of abortion decision-making, this typically takes place before women approach healthcare professionals for help with accessing the procedure (Allen, 1985; Brown, 2013; Kumar, Baraitser, Morton, & Massil, 2004; Lee, 2004). While women do not generally want input into their decision-making, their interactions with healthcare services are nonetheless central in their experiences of their decisions as either socially legitimate or as problematic (Allen, 1985; Astbury-Ward et al., 2012; Harden & Ogden, 1999; Kumar et al., 2004; Lee, 2004; Purcell, Cameron, et al., 2014).…”
Section: Women’s Experiences With Abortion In Great Britainmentioning
confidence: 99%